Search for narrow resonances and quantum black holes in inclusive and $b$-tagged dijet mass spectra from $pp$ collisions at $\sqrt{s}=7$ TeV - CMS collaboration (2217 authors) (2013)
A search for narrow resonances and quantum black holes is performed in inclusive and b-tagged dijet mass spectra measured with the CMS detector at the LHC. The data set corresponds to 5 inverse femtobarns of integrated luminosity collected in pp collisions at sqrt(s) = 7 TeV. No narrow resonances or quantum black holes are observed. Model-independent upper limits at the 95% confidence level are obtained on the product of the cross section, branching fraction into dijets, and acceptance for three scenarios: decay into quark-quark, quark-gluon, and gluon-gluon pairs. Specific lower limits are set on the mass of string resonances (4.31 TeV), excited quarks (3.32 TeV), axigluons and colorons (3.36 TeV), scalar color-octet resonances (2.07 TeV), E(6) diquarks (3.75 TeV), and on the masses of W' (1.92 TeV) and Z' (1.47 TeV) bosons. The limits on the minimum mass of quantum black holes range from 4 to 5.3 TeV. In addition, b-quark tagging is applied to the two leading jets and upper limits are set on the production of narrow dijet resonances in a model-independent fashion as a function of the branching fraction to b-jet pairs.